Presence and Location of CatSper 1–4, Opioid (μ, δ and κ) and CD44 Receptors in Spermatozoa from Aoudad, Iberian Ibex and Mouflon - Alejandro Vicente‐Carrillo; Manuel Álvarez‐Rodríguez; Cristina Castaño; Adolfo Toledano‐Díaz; Eva Martínez‐Nevado; Heriberto Rodríguez‐Martínez; Julián Santiago‐Moreno (Veterinary Medicine and Science)
ABSTRACT Despite the apparent progress in reproductive technologies in wild ruminant species, healthy live births have been limited. Acquiring a sound knowledge of the molecular basis of most functional aspects of spermatozoa will improve the effectiveness of reproductive techniques and optimise conservation programs for threatened species. CatSper channels, opioid receptors and CD44 are involved in sperm capacitation of humans and domestic animals, but their presence in wild ruminants is yet undisclosed. The aim of this study was to determine the presence and localisation of CatSper 1–4, μ, δ and κ‐opioid receptors and CD44 in three wild ruminant species spermatozoa (aoudad [n = 5], Iberian ibex [n = 5], mouflon [n = 5]), which show different resistance to freezing‐thawing processes. Western blotting (WB) and immunocytochemistry (ICC) performed with commercially available antibodies revealed that aoudad, Iberian ibex and mouflon are equipped with the aforementioned channels and receptors, sharing localisation with other domestic animals’ spermatozoa but presenting species‐particularities. WB revealed homogeneous results in CatSper 1, Catsper 2, Catsper 3 and CatSper 4 among the spermatozoa of the three species, unlike μ, δ and κ‐opioid and CD44 receptors that showed substantial inter‐species differences in the number of bands. ICC showed inter‐species differences in the location of CatSper 1–4, μ, δ and κ‐opioid and CD44 receptors. Data confirmed their presence and putative role on sperm function in wild ruminant species. Inter‐species differences in the location of CatSper 1–4, μ, δ and κ‐opioid and CD44 receptors might underlie the variable response to reproductive technologies in these species.